Properties of Hydroxyapatite Coatings on Metal Oxide - V.V. Starikov (Журнал нано- та електронної фізики)
The hydroxyapatite coating Ca10(PO4)6(OH)2 was formed on the oxidized niobium surface by RF magnetron sputtering method using hydroxyapatite and three calcium phosphate targets. The structure, substructure and mechanical properties of the Nb-Nb2O5-HAP system were investigated by X-ray diffraction, atomic force microscopy, nanoindentation, as well as an assessment of the stress state in such system. Synthesized hydroxyapatite film had the following characteristics: the thermal expansion coefficient αHA = 1 × 10 – 5 К – 1; elasticity modulus ЕHA = 120 GPa; adhesive strength was not less than 0.45 kg/mm2; density 2900 kg/m3. The stress magnitude in the metal-oxide substrate was from 11 to 14 MPa at hydroxyapatite films deposition.